Analysis of the Effect of Self-Efficiency Mediation and Organizational Commitment on the Influence of Culture of Performance and Employee Satisfaction - Netty Laura Simbolon; Budi Satriyo Priyonggo (Publikasi Indonesia, 2022)
A company cannot develop optimally if it is not fully supported by qualified and advanced human resources within the company, including PT Sarana Lintas Caraka. The purpose of this study was to examine the mediating effect of self-efficacy and organizational commitment on the effect of organizational culture on employee performance and job satisfaction at PT Sarana Lintas Caraka. The research method used in this research is quantitative with Partial Least Square (PLS-SEM) technique and assisted by software SmartPLS 3.0The researcher chose the census technique in the sampling technique, namely all members of the population (all PT Sarana Lintas Caraka) were used as samples in this study to examine the mediating effect and the direct influence of the related variables. The results of this study indicate that there is an influence of organizational culture on employee performance, the influence of organizational culture on employee job satisfaction, the influence of self-efficacy on employee performance, self-efficacy has no effect on employee job satisfaction, organizational commitment does not affect employee performance, the influence of organizational commitment on employee job satisfaction, self -efficacy is able to mediate the influence of organizational culture on employee performance, self-efficacy is not able to mediate the influence of organizational culture on employee job satisfaction, organizational commitment is not able to mediate the influence of organizational culture on employee performance, organizational commitment is able to mediate the influence of organizational culture on employee job satisfaction. The method of determining the number of respondents' eligibility uses the Hair Method which states that the respondent may be 5 to 10 times the number of indicators of research variables.